ANALISIS METAKOGNISI SISWA DALAM MEMECAHKAN MASALAH BARISAN DAN DERET BILANGAN DITINJAU DARI KEMAMPUAN MATEMATIS - Hanief Maulana; Abdur Rohim (INSPIRAMATIKA, 2021)
The purpose of this study was to describe the metacognition of XI grade students of SMA Hasyim Asy'ari 1 Pucuk in problem solving of sequences and series of numbers in high, medium and low ability students. This research is a descriptive qualitative research conducted online using whatsapp social media. The research instrument is the researcher himself supported by written tests and interviews. The subjects of this study were six students consisting of one student with high ability, two students with moderate ability and two students with low ability. The results of this study indicate that students with high abilities have good declarative knowledge, procedural knowledge and conditional knowledge. Students with high abilities are also able to use good planning skills, monitoring skills and evaluation skills. Students with moderate ability have declarative knowledge, good procedural knowledge and good conditional knowledge. Students with moderate abilities are also able to use planning skills, monitoring skills well and do not have evaluation skills. Students with low abilities only have declarative knowledge. Students with low abilities also only use planning skills.